Dose and dose-rate dependency in the mortality response of Calanus finmarchicus embryos exposed to ultraviolet radiation - Browman, Howard I.; St-Pierre, Jean-François; Kuhn, Penelope S. (Marine Ecology Progress Series, 2003)
In previous work, we reported that embryos of Calanus finmarchicus exposed to artificial ultraviolet-B (UV-B) radiation exhibited high wavelength-dependent mortality. The strongest effects occurred under exposures to wavelengths below 312 nm and, at the shorter wavelengths (<305 nm), UV-B-induced mortality was strongly dependent on cumulative exposure (i.e. dose). In the experiments reported here, we tested (for C. finmarchicus) the principle of reciprocity - that is, was the effect of cumulative UV dose the same regardless of the dose rate at which it was delivered? Dose rate had no discernible effect on the proportion of live C. finmarchicus nauplii recovered from eggs exposed to 3 different UV doses: reciprocity held. The doses and dose rates administered were ecologically relevant. However, the issue of UV dose versus dose-rate effects on marine organisms requires further investigation at a broad range of dose and dose rates and for different exposure durations, preferably under natural sunlight.